2008
DOI: 10.1089/neu.2007.0386
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Serum Biomarkers in Brain-Injured Adults: Potential for Predicting Elevated Intracranial Pressure

Abstract: Brain injury biomarkers may have clinical utility in stratifying injury severity level, predicting adverse secondary events or outcomes, and monitoring the effectiveness of therapeutic interventions. As a biomarker source, serum offers several advantages over cerebrospinal fluid (CSF), including ease of accessibility and reduced risk to the patient. We screened pooled serum samples obtained from 11 severely injured traumatic brain injury (TBI) patients (Glasgow Coma Scale [GCS] Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(75 citation statements)
references
References 48 publications
1
74
0
Order By: Relevance
“…As an example of using serum samples from severely injured TBI patients and healthy volunteer controls, C-reactive protein and serum amyloid A have been reported to be capable of distinguishing between these two groups. 8 However, both of these proteins are general indicators of injury/infection, making them less likely to distinguish brain injury patients from persons with other bodily injuries. On the other hand, if brain injury alone is suspected, or if these markers were used in combination with other biomarkers, a rise in the levels of these proteins in serum may further support a brain injury diagnosis.…”
Section: Tbi Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations
“…As an example of using serum samples from severely injured TBI patients and healthy volunteer controls, C-reactive protein and serum amyloid A have been reported to be capable of distinguishing between these two groups. 8 However, both of these proteins are general indicators of injury/infection, making them less likely to distinguish brain injury patients from persons with other bodily injuries. On the other hand, if brain injury alone is suspected, or if these markers were used in combination with other biomarkers, a rise in the levels of these proteins in serum may further support a brain injury diagnosis.…”
Section: Tbi Biomarkersmentioning
confidence: 99%
“…For example, it has been reported that the acute phase reactant proteins C-reactive protein and serum amyloid A are rapidly increased in the serum of brain trauma patients. 8 Using a multiplex approach to simultaneously evaluate a panel of chemokines and cytokines, Buttram et al 44 reported that severe TBI in children was associated with significant increases in the CSF levels of interleukin (IL)-1␤, IL-6, IL-12p70, IL-10, IL-8, and MIP-1␣. Because the injury to other organs can increase the serum level of these markers, these markers by themselves may not provide high specificity.…”
Section: Inflammatory Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathogenesis of vasospasm is due to smooth muscle contraction (entry and release of calcium and activation of calcium / calmodulin-dependent myosin light-chain kinase), endothelial injury (nitric oxide and endothelin-1 derangement), inflammation (inflammatory cytokines, intercellular adhesion molecules and genetic upregulation of inflammatory, proliferative and extracellular matrix-regulating genes) and vessel remodeling 1,3,[10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…The levels of hemoglobins were significantly increased over time, which correlates well with the expected increase of erythrocytes after intracranial bleeding 4-19 days after injury and their haemolysis that starts after approximately 12 h. Among the findings shown in Table 1, acute-phase, and thereto-related proteins, as well as other high abundant proteins such as albumin, immunoglobulins, hemoglobins and transferrin were detected. Acute-phase proteins have been described to be involved in the protection of the injured area as a response to prevent cell death [29,32] while increased levels of protease inhibitors, such as Cystatin C, have been related to an auto-protective brain response to protease hyper activation [29,33]. The fibrinogens identified in the vCSF sample could hypothetically be a blood contamination of CSF or a consequence of damage on the blood-CSF barrier.…”
Section: Proteomic Investigation Of Vcsf From a Tbi Patientmentioning
confidence: 99%